ASYMMETRICAL FOUR U-SLOTS MICRO-STRIP CIRCULAR PATCH ANTENNA FOR WLAN AND WI-FI COMMUNICATION APPLICATIONS - Arshad Wahab; Waleed Ahmad; Muhammad Kashif Khattak; Bilal Ahmad; Aamir Hayyat; Anum Mushtaq (Spectrum of Engineering Sciences, 2025)
The modern communication systems require broad band, compact size and multipurpose antennas for the emerging technologies like 5G and satellite communication. The limitations of micro strip patch antennas include narrow bandwidths and low gains, which make it incompatible with the modern communication systems. The proposed antenna is composed of asymmetrical four U-slots in the patch. The slots are introduced to obtain the broadband characteristics of the antenna. The parameters such as changing the width and length of the U-slots, the radius of the patch and variation in feed point location can improve the efficiency and can remove the bottlenecks of the microstrip patch antennas. The proposed antenna is designed for WLAN and Wi-Fi applications. The aim is to analyze parametric studies and to discuss about how the variations in different parameters of antenna can enhance the gain and the narrow bandwidth. The size and weight of the antenna will be reduced by using an air substrate between the patch and ground.